The Prevalence of Weak Handgrip Strength in Ambulatory Oncology Patients and its Relationship with Quality of Life - Niamh O'Callaghan; Aoibheann O Sullivan; Catherine McHugh; Laura Keaver (SURE Journal: (Science Undergraduate Research Experience Journal))
Muscle strength as a proxy for muscle function has emerged as a predictor of nutritional status in both clinical as well as epidemiological studies. Hand grip strength (HGS) is a reliable non-invasive test of muscle strength. Dynapenia (weak strength) is independently associated with loss of physical functionality, quality of life (QoL) characteristics and reduced survival. The first aim of this study was to investigate the prevalence of dynapenia using handgrip strength (HGS) in ambulatory oncology patients and if this had an impact on quality of life (QoL). This prospective cross-sectional study was conducted in the oncology day ward and outpatient clinic in Sligo University Hospital (SUH). To assess QoL, participants completed the European Organisation for Research and Treatment of Cancer Quality-of-life Questionnaire Core 30 (EORTC QLQ-C30). Isometric handgrip dynamometry was used to determine muscle strength of the dominant forearm. Three measures were performed, and the highest value was analysed. Weak handgrip strength was defined as(n=160) was predominantly female (58.1%), breast cancer was the most prevalent cancer type (29.4%) and the mean age was 63.2 ± 11.3 years. Over half of the cohort was overweight (53.5%) and 70% had not received nutritional advice from a dietician, with 77.5% reporting weight changes since diagnosis. Weak handgrip strength was present in 26.9% of the cohort. Weaker HGS was significantly associated with poorer QoL, physical, role and cognitive functioning (p < 0.05). Additionally, weaker HGS was associated with increased symptom scale scores for fatigue, pain and appetite loss (p < 0.05). Results display how poor muscular strength impacts QoL in an ambulatory oncology setting in the North-West of Ireland. If routine screening of muscle strength was conducted in oncology patients, it could aid timely referral to nutrition support and combat the negative impacts on their future.